Minimum wage reform and firms' performance - Evidence from North Macedonia - Biljana Jovanovic; Nikola Naumovski (National Bank of the Republic of North Macedonia, 2021)
Minimum wage is an important redistributive tool and an important element of the employment strategies and social policies for overcoming poverty and reducing inequality. Even though the social dimension of the minimum wage concept is unquestionable, it also provokes frequent debates and discussions about the likely impact on firms' financial conditions and consequently, firms' profitability and performance. This research paper aims to investigate the economic impact of minimum wage increase on firms' average wages, number of employees, profitability and productivity in the case of North Macedonia. The analysis is conducted by using firm level data set and difference-in-difference (DD) estimation method. Our results showed that the increase in minimum wages didn't affect firms' profitability significantly and this result is robust to the changes in the sample and method of estimation. In addition we found that most likely Macedonian firms did absorb higher labour costs by increase in productivity and, in some sectors, with decline in employment.
Keywords: J31; J38; L25; 330; minimum wage; adjustment channels; firms' performance